Pengaruh Proses Rekrutmen, Seleksi, dan Training Terhadap Kinerja Karyawan Produksi Di PT SML Indonesia Private - Sriyati; Rr. Hawik Ervina I; Ratih Hesty (PT. Hasba Edukasi Mandiri, 2025)
The Hiring Process Is Not An Easy Or Straightforward Activity. This Turns Out To Be Quite Complicated, Time-Consuming, And Expensive, And There Is A High Probability That The Wrong Candidate Will Be Selected. As A Result, Candidates Are Sought, And Applications Are Closed. The Application Letter Is Submitted In Accordance With The Requirements Set By The Party Company. The Result Is A Group Of Job Seekers Where New Employees Who Will Be In The Next Stage Are Carried Out In The Selection Process. This Study Uses A Quantitative Research Method. The Population Used Is The Total Number Of Employees At Pt Sml Indonesia Private As Many As 150 Employees. The Sampling Process Uses Nonprobability Sampling. In This Study, The Technique Used In Obtaining And Collecting Data Is Using Questionnaires. The Result Of This Study Is An Alpha Value Of 0.487 Out Of 6 Questions In The Recruitment Variable. The Alpha Value Was 0.194 Out Of 10 Questions In The Training Variable. The Alpha Value Was 0.019 Out Of 10 Questions In The Selection Variable. The Alpha Value Is 0.375 Out Of 10 Statement Items In The Employee Performance Variable. The Conclusion Of This Study Is That The Recruitment Process At Pt. Sml Indonesia Private, Semarang, Is Carried Out According To Predetermined Procedures Through Internal And External Methods, Including Advertising And Cooperation With Universities And The Ministry Of Education, So That The Hypothesis Is Proven Correct. Recruitment Is Proven To Have A Positive And Significant Influence On The Quality Of Employee Work With A Frequency Of 0.325. In Addition, The Selection Also Shows A Positive And Significant Influence On Employee Performance, As Well As Training That Has A Similar Impact On Employee Performance In The Company.